2005
DOI: 10.1073/pnas.0502935102
|View full text |Cite
|
Sign up to set email alerts
|

VEGF–integrin interplay controls tumor growth and vascularization

Abstract: Cross-talk between the major angiogenic growth factor, VEGF, and integrin cell adhesion receptors has emerged recently as a critical factor in the regulation of angiogenesis and tumor development. However, the molecular mechanisms and consequences of this intercommunication remain unclear. Here, we define a mechanism whereby integrin ␣v␤3, through activation, clustering, and signaling by means of p66 Shc (Src homology 2 domain containing), regulates the production of VEGF in tumor cells expressing this integri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
113
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(119 citation statements)
references
References 30 publications
(27 reference statements)
5
113
0
1
Order By: Relevance
“…Intestinal smooth muscle cells express ␣V␤3, and blocking ligand occupancy of this integrin inhibits IGF-I actions (45). Endothelial cells have abundant ␣V␤3, which can function to localize Shc to the cell membrane (41,46), and our studies have shown that blocking ligand occupancy of endothelial ␣V␤3 attenuates IGF-I-stimulated Shc activation and cell growth. Skeletal unloading results in decreased ␣V␤3 expression in osteoblasts, and they become refractory to stimulation of the MAP kinase pathway activation and growth by IGF-I (47).…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal smooth muscle cells express ␣V␤3, and blocking ligand occupancy of this integrin inhibits IGF-I actions (45). Endothelial cells have abundant ␣V␤3, which can function to localize Shc to the cell membrane (41,46), and our studies have shown that blocking ligand occupancy of endothelial ␣V␤3 attenuates IGF-I-stimulated Shc activation and cell growth. Skeletal unloading results in decreased ␣V␤3 expression in osteoblasts, and they become refractory to stimulation of the MAP kinase pathway activation and growth by IGF-I (47).…”
Section: Discussionmentioning
confidence: 99%
“…These observations are in accord with our previous studies demonstrating that VEGF is a potent stimulator of the ␣V␤3 activation and ␣V␤3-dependent EC functions via VEGFR2-dependent inside-out signaling. 6,7 Thus, the kindlin-2 ϩ/Ϫ phenotype demonstrates a critical role of ␤3 integrins in angiogenesis in vivo in the absence of compensatory increases in VEGFR2. However, kindlin-2 also promotes the ␤3 integrin functions via other inside-out signaling pathways, for example, PKC-dependent For personal use only.…”
Section: Discussionmentioning
confidence: 99%
“…6 Indeed, VEGFR2 and integrin ␣V␤3 can form a physical complex in EC and influence the functions of each other. 6,7 Two sets of cytoskeletal proteins, the talins and the kindlins, bind to the ␤ cytoplasmic tails and are now known to be involved in integrin activation. [8][9][10] Talin has long been known to be critical for integrin activation 11 and more recent studies have shown an obligatory requirement for the kindlins in integrin activation in the context of intact cells and whole organisms.…”
Section: Introductionmentioning
confidence: 99%
“…VEGF is known to exert an autocrine as well as paracrine mitogenic effect on a variety of tumor cells including melanoma, prostate cancer, and ovarian cancer in vivo (22,(35)(36)(37)(38). Our pilot studies indicated that VEGF stimulates the proliferation of ID8 cells in a concentration-dependent manner (data not shown).…”
Section: Sparc Inhibits Vegf-induced Proliferation and Survival Of Ovmentioning
confidence: 99%